Impact of COVID-19 Pandemic on Intervals and Outcomes of Repeated Transarterial Chemoembolization in Patients With Hepatocellular Carcinoma - Jin, Zhi-Cheng; Chen, Li; Zhong, Bin-Yan; Zhu, Hai-Dong; Zeng, Chu-Hui; Li, Rui; Guo, Jin-He; He, Shi-Cheng; Deng, Gang; Zhu, Xiao-Li; Ni, Cai-Fang; Teng, Gao-Jun (Frontiers in Oncology, 2021)
Purpose: Given that the novel coronavirus disease (COVID-19) pandemic has disrupted operations globally, an institution's ability to repeat transarterial chemoembolization (TACE) for patients with hepatocellular carcinoma (HCC) has also been affected. The aim of this study was to evaluate the impact of the COVID-19 on the intervals and outcomes of TACE in HCC patients. Materials and Methods: This retrospective study included 154 HCC patients who underwent follow-up after TACE treatment from January 2020 to March 2020 (n = 71, study group) and January 2019 to March 2019 (n = 83, control group) at two institutions in China. The endpoints included the follow-up interval and overall response rate (ORR). Multivariate logistic regression analyses were performed to identify independent risk factors for a worse ORR. The cut-off point was determined to divide follow-up durations into long- and short- intervals. Results: The median follow-up interval was 82.0 days (IQR, 61–109) in the study group, which was significantly longer than 66.0 days (IQR, 51–94) in the control group (P = 0.004). The ORR was 23.9% and 39.8% in the study and control group, respectively (P = 0.037). The cut-off value was 95 days. The grouping (OR, 2.402; 95% CI, 1.040–5.546; P = 0.040), long interval (OR, 2.573; 95% CI, 1.022–6.478; P = 0.045), and China liver cancer staging system (OR, 2.500; 95% CI, 1.797–3.480; P < 0.001) were independent predictors for the efficacy of TACE treatment. Conclusions: The COVID-19 pandemic causes a longer follow-up interval in general, which may further lead to a lower ORR in HCC patients. Those with a follow-up interval of > 95 days tend to have a worse prognosis.